Enhancing methane production from U. lactuca using combined anaerobically digested sludge (ADS) and rumen fluid pre-treatment and the effect on the solubilization of microbial community structures. (April 2018) - Zou, Yu; Xu, Xiaochen; Li, Liang; Yang, Fenglin; Zhang, Shushen
Highlights: Rumen fluid pre-treatment + co-fermentation with rumen fluid and ADS are effective in enhancing anaerobic methane production from U. lactuca. Both the hydrolysis rate and biochemical methane potential of U. lactuca are improved through a combination of co-fermentation and rumen fluid pre-treatment. The combination of co-fermentation and rumen fluid pre-treatment achieves higher anaerobic methane production than co-fermentation or rumen fluid pre-treatment alone. Abstract: Methane production by the anaerobic digestion of seaweed is restricted by the slow degradation caused by the influence of the rigid algal cell wall. At the present time, there has been no study focusing on the anaerobic digestion of U. lactuca by co-fermentation and pre-treatment with rumen fluid. Rumen fluid can favor methane production from algal biomass by utilizing the diversity and quantity of bacterial and archaeal communities in the rumen fluid. This research presents a novel method based on combined ADS and rumen fluid pre-treatment to improve the production of methane from seaweed. Biochemical methane potential (BMP) tests were performed to investigate the biogas production using combined ADS and rumen fluid pre-treatment at varied inoculum ratios on the performance of methane production from U. lactuca biomass. Compared to the control (no rumen fluid pre-treatment), the highest BMP yields of U. lactuca increased from 3%, 27.5% and 39.5% to 31.1%, 73% and 85.6%, respectively, for three different types of treatment. Microbial community analysis revealed that the Methanobrevibacter species, known to accept electrons to form methane, were only detected when rumen fluid was added. Together with the significant increase in species of Methanoculleus, Methanospirillum and Methanosaeta, rumen fluid improved the fermentation and degradation of the microalgae biomass not only by pre-treatment to foster cell-wall degradation but also by relying on methane production within itself during anaerobic processes. Batch experiments further indicated that rumen fluid applied to the co-fermentation and pre-treatment could increase the economic value and hold promise for enhancing biogas production from different seaweed species.